The moderation of satisfaction with working conditions in the association between workload and mental health among healthcare workers collecting test samples in the post-COVID-19 era - Wang, Kehui; Yang, Bin; Wu, Cuiping; Zheng, Lianxue (Frontiers in Public Health, 2023)
Abstract Background: This study aimed to examine the associations between workload and satisfaction with working conditions with mental health(i.e. anxiety disorder, depression and somatization) of healthcare workers collecting test samples during the local outbreaks of COVID-19, and explore satisfaction with working conditions as a moderator of these relationships. Methods: A total of 1,349 participants were obtained via an online survey in Zhengzhou, Henan Province, China. Multivariate regression was used to assess the associations between workload and satisfaction with working conditions with anxiety disorder, depression, and somatization. The simple slope analysis and Johnson-Neyman technique was used to assess the effect value and change trend of the moderator. Results: The prevalence of anxiety disorder, depression and somatization were 8.6%, 6.9% and 19.2% of healthcare workers collecting test samples, respectively. High levels of workload were associated with an increased risk of anxiety disorder(OR=1.81, 95%CI=1.17-2.78), depression(OR=1.92, 95%CI =1.19-3.10), and somatization(OR=1.90, 95%CI=1.40-2.57), while high satisfaction of working conditions was associated with a reduction in the risk of these outcomes, OR(95%CI) were 0.35(0.20-0.64), 0.27(0.13-0.56), and 0.32(0.21-0.48), respectively. The findings also indicated that a weaker association between workload and anxiety disorder, as well as depression and somatization, has been reported in those with a high level of satisfaction with working conditions. Conclusions: Workload significantly increased the risk of healthcare workers suffering from psychological problems, while satisfaction with working conditions alleviated these negative effects, and effective resource support was crucial for healthcare workers.